Maqâmat al-Sâlik li al-Wushȗl Ila al-Khâliq (Ringkasan Kitab Minhâj al-‘Abidîn Ilâ Jannati Rabbil ‘Alamîn) Karya Hujjatul Islam Imam al-Ghazali - Dahri, Haji Harapandi (Borneo International Journal of Islamic Studies, 2018)
Every man wants to be close to God as Creator, even though not conscious, humans long for His presence every moment especially when getting difficulty and tiredness, longing to be close to Him is nature. Hujat al-Islam Imam al-Ghazali never felt the same, because that is what he poured great ideas, method of finding and approaching the real Maha close in a work given the title "Minhâj al-'Abidîn Ilâ Jannati Rabbil 'Alamîn" . In this book there are seven (7) steps that will be passed by the seeker of the road to get closer to Allah Azza Wajalla. The seven steps are (1) al-science wa al-Marifah, (2) al-Taubat, (3) al-Awâiq, (4) al-Awârid, (5) al-Bawâits, (6) al-Qawâdih and (7) al-Hamd wa al-Syukr. Between one step with the next step interconnected. Every human being who works without knowledge must be losers, his charity will not be accepted by Allah, because it requires knowledge and knowledge. In charity there is a defect either forget (nisyan) or deliberately (amdan), because that's give the media to repent. After repentance humans back clean, but in worship there is a very powerful challenge like the world, creatures, syaithan and also lust, because it needs cleaning, this cleansing position is called al-Awâiq. After knowing the rackets in worship, it is necessary to cleanse themselves of the various challenges that is why al-Shaykh gave aqabah onwards al-Awârid. At aqabah this will explain how to overcome these challenges. And so on until to the maqam al-Hamd wa al-Syukr. These seven aqabât are to be discussed in this paper.